Challenges of Islamic Religious Higher Education in Indonesia: Qualitative Analysis Using NVivo Software - Septa Riadi; Ahiruddin Ahiruddin; Kuswarak Kuswarak; Husna Purnama (Journal Corner of Education, Linguistics, and Literature, 2021)
This study aims to analyze and examine the main issues in any news on the internet related to the challenges of Islamic Religious Higher Education. Online News is obtained using the Google Indonesia search engine using the keyword "PTKI Challenge". In this study, 22 most popular news items were analyzed related to these keywords. All the news is then coded to find the main topic contained in the news using NVivo version 12 software. The results of the main topic analysis show that the PTKI Challenge according to various news quotes has revealed many things with 58 references obtained by researchers from 22 online news. The 58 references are divided into twenty main topics. Of the 20 main topics mentioned above, the most highlighted challenge was "the curriculum does not fit the needs" which were quoted from 8 references. Next, the most cited challenge for PTKI is the “Pandemic” which throughout 2020 is currently hitting Indonesia with 6 references. Furthermore, the challenge for PTKI that was highlighted the most was Institutional Strengthening, totaling 6 citations. And also widely quoted is the acquisition of skills and knowledge in PTKI which is a challenge with as many as 6 references.